Edukasi Pemanfaatan Lahan dan Sampah Anorganik Warga Terdampak Covid-19 di Desa Cikeas - Farell Pramuja; Aldo Reshwara; Hirda Umayyah; Ravellino Fahlepi; Iffani Nabila Zain; Muhammad Zaki Dama; Nur Shasqia Malewa; Shabrina Itsnaini Oktafira; Sita Permata Sari; Bustami Bustami (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2021)
Cikeas Village is located in Sukaraja District, Bogor Regency and is one of locations for IPB Student Community Service. Before going to field, students are given with knowledge of regional potential and community empowerment lesson so that program implementation can run well. The purpose of this activity is hydroponic cultivation training and product agribusiness planning to increase community productivity and resolve waste problems. The program carried out is socialization hydroponic cultivation and the utilization of inorganic waste. Output expected is that residents can mix and provide nutrients according to the type of hydroponic plants properly and open people's insights on importance of processing waste and its potential for using waste into useful items. At the end, hydroponic cultivation module which arranged by the student team was also given to community in Cikeas Village. Keywords: hydroponics, garbage, land use